Learning from master of education students’ experiences in an accelerated online program at a Hispanic-serving institution - Lu, Pierre; Masri, Taghreed; Garcia, Tania (Journal of Education and e-Learning Research, 2025)
The study aimed to explore Master of Education students’ experiences in an accelerated online program, addressing whether course design and instructional practices met student expectations. Using a mixed-methods research design, the study collected data from 204 students through an online survey conducted from 2019 to 2023. The participants were predominantly female (80%) and Hispanic (77%), with the majority enrolled in elementary math and science education (42.6%), followed by content English (26.5%), mathematics education (20.6%), and content mathematics (4.4%). Data analysis included exploratory data analysis (EDA), correlation analysis, ANOVA, and t-tests to identify trends in student feedback. Key findings emphasized the importance of comprehensive program evaluation frameworks and the benefits of condensed course structures and assignment breakdowns. Additionally, effective faculty preparation was linked to positive student experiences, particularly when instructors were both subject-matter experts and skilled in teaching adult learners. Experiential learning was shown to improve engagement and skill development. This study contributes to understanding how accelerated Master of Education programs can be optimized by balancing content delivery, instructional quality, and student workload to foster both professional growth and academic success.